Activating transcription factor 4-dependent lactate dehydrogenase activation as a protective response to amyloid beta toxicity. Issue 2 (26th March 2021) - Niccoli, Teresa; Kerr, Fiona; Snoeren, Inge; Fabian, Daniel; Aleyakpo, Benjamin; Ivanov, Dobril; Sofola-Adesakin, Oyinkan; Cryar, Adam; Adcott, Jennifer; Thornton, Janet; Partridge, Linda
Abstract: Accumulation of amyloid beta peptides is thought to initiate the pathogenesis of Alzheimer's disease. However, the precise mechanisms mediating their neurotoxicity are unclear. Our microarray analyses show that, in Drosophila models of amyloid beta 42 toxicity, genes involved in the unfolded protein response and metabolic processes are upregulated in brain. Comparison with the brain transcriptome of early-stage Alzheimer's patients revealed a common transcriptional signature, but with generally opposing directions of gene expression changes between flies and humans. Among these differentially regulated genes, lactate dehydrogenase ( Ldh ) was up-regulated by the greatest degree in amyloid beta 42 flies and the human orthologues ( LDHA and LDHB ) were down-regulated in patients. Functional analyses revealed that either over-expression or inhibition of Ldh by RNA interference (RNAi) slightly exacerbated climbing defects in both healthy and amyloid beta 42-induced Drosophila . This suggests that metabolic responses to lactate dehydrogenase must be finely-tuned, and that its observed upregulation following amyloid beta 42 production could potentially represent a compensatory protection to maintain pathway homeostasis in this model, with further manipulation leading to detrimental effects. The increased Ldh expression in amyloid beta 42 flies was regulated partially by unfolded protein response signalling, as ATF4 RNAi diminished the transcriptional response and enhanced amyloid beta 42-induced climbing phenotypes. Further functional studies are required to determine whether Ldh upregulation provides compensatory neuroprotection against amyloid beta 42-induced loss of activating transcription factor 4 activity and endoplasmatic reticulum stress. Our study thus reveals dysregulation of lactate dehydrogenase signalling in Drosophila models and patients with Alzheimer's disease, which may lead to a detrimental loss of metabolic homeostasis. Importantly, we observed that down-regulation of ATF4 -dependent endoplasmic reticulum-stress signalling in this context appears to prevent Ldh compensation and to exacerbate amyloid beta 42-dependent neuronal toxicity. Our findings, therefore, suggest caution in the use of therapeutic strategies focussed on down-regulation of this pathway for the treatment of Alzheimer's disease, since its natural response to the toxic peptide may induce beneficial neuroprotective effects. Abstract : Niccoli et al. report, in Drosophila, that neuronal lactate dehydrogenase, through activating transcription factor 4, is increased in response to Aβ42. Conversely, lactate dehydrogenase is reduced in inhibitory neurons, which are vulnerable to neurodegeneration in Alzheimer's disease patients. It is therefore possible that upregulation of Ldh maintains neuronal homeostasis. Graphical Abstract: